Advance care planning – out goes paternalism, in comes consultative conversation. Issue 1 (1st June 2011) - Finlay, I
Abstract : We all know what we want – or do we? Patients cannot 'choose' to not be ill or avoid dying of their disease, but deserve be involved in decisions about their care. UK Mental Capacity legislation heralded a long-overdue change, encapsulated in the NHS slogan 'no decision about me without me'; everyone must to do everything to maximise patients' decision-making ability. Impediment of brain function cannot be assumed to render decisions invalid; if decision-making capacity for a particular decision is lacking, then previously expressed wishes must be considered when making a decision in a person's best-interest . Personhood is a function of being alive; after death one is a corpse. So, best interest to relieve suffering may necessitate risk-taking, but does not include deliberately killing the person. Advance Decisions to refuse treatment (aka Advance Directives/Living Wills) if competently drawn up and relevant to the specific situation are legally binding, signalling the person has already withheld consent to a particular intervention; they cannot direct in advance that something is done, neither drug treatment nor surgery nor lethal overdose. In ethical equipoise is an advance statement of wishes – to be considered if lack of capacity requires a best-interest decision. Advance care planning (ACP) maintains this equipoise; calm timely discussions can 'plan for the worst and hope for the best'. Open, realistic conversations address concerns, avoid false reassurance, and honestly discuss options. Honest ACP can reveal service deficits that militate against excellent care, galvanising action to improvements in care.